Light-dependent modulation of protein localization and function in living bacteria cells - Ryan McQuillen; Amilcar J. Perez; Xinxing Yang; Christopher H. Bohrer; Erika L. Smith; Sylvia Chareyre; Ho-Ching Tiffany Tsui; Kevin E. Bruce; Yin Mon Hla; Joshua W. McCausland; Malcolm E. Winkler; Erin D. Goley; et al. (Nature Communications)
Abstract Most bacteria lack membrane-enclosed organelles and rely on macromolecular scaffolds at different subcellular locations to recruit proteins for specific functions. Here, we demonstrate that the optogenetic CRY2-CIB1 system from Arabidopsis thaliana can be used to rapidly direct proteins to different subcellular locations with varying efficiencies in live Escherichia coli cells, including the nucleoid, the cell pole, the membrane, and the midcell division plane. Such light-induced re-localization can be used to rapidly inhibit cytokinesis in actively dividing E. coli cells. We further show that CRY2-CIBN binding kinetics can be modulated by green light, adding a new dimension of control to the system. Finally, we test this optogenetic system in three additional bacterial species, Bacillus subtilis, Caulobacter crescentus, and Streptococcus pneumoniae, providing important considerations for this system’s applicability in bacterial cell biology.